2012
DOI: 10.3945/jn.111.153411
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Reveals Differences in Umbilical Vein Plasma Metabolites between Normal and Growth-Restricted Fetal Pigs during Late Gestation

Abstract: Intrauterine growth restriction (IUGR) remains a major problem for both human health and animal production due to its association with high rates of neonatal morbidity and mortality, low efficiency of food utilization, permanent adverse effects on postnatal growth and development, and long-term health and productivity of the offspring. However, the underlying mechanisms for IUGR are largely unknown. In this study, one IUGR fetus and one normal body weight (NBW) fetus were obtained from each of 9 gilts at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
78
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 55 publications
15
78
2
Order By: Relevance
“…However, this pattern was not related to a higher birth weight or a higher growth rate in the first days of life, which resembles the results from previous studies carried out on the first generation of Iberian pigs exposed to prenatal programming (Barbero et al 2013). Our findings are in agreement with those of previous studies which indicate that, in pigs, growth and maturation of foetuses are markedly determined during the last few days of gestation (McPherson et al 2004, Foxcroft et al 2006, Lin et al 2012, even more in antique breeds such as Iberian swine (Charneca et al 2010). This ability to modulate terminal foetal growth may explain the lack of differences among newborns programmed either by nutritional excesses or deficiencies and nonchallenged (Ravelli et al 1976, Roseboom et al 2001.…”
Section: Discussionsupporting
confidence: 83%
“…However, this pattern was not related to a higher birth weight or a higher growth rate in the first days of life, which resembles the results from previous studies carried out on the first generation of Iberian pigs exposed to prenatal programming (Barbero et al 2013). Our findings are in agreement with those of previous studies which indicate that, in pigs, growth and maturation of foetuses are markedly determined during the last few days of gestation (McPherson et al 2004, Foxcroft et al 2006, Lin et al 2012, even more in antique breeds such as Iberian swine (Charneca et al 2010). This ability to modulate terminal foetal growth may explain the lack of differences among newborns programmed either by nutritional excesses or deficiencies and nonchallenged (Ravelli et al 1976, Roseboom et al 2001.…”
Section: Discussionsupporting
confidence: 83%
“…These lower concentrations of 5-HT in SGA piglets might be attributed to a fall in the number of platelets, as already described in low birth weight infants (Christensen et al, 2006). Another study in foetal piglets also described lower foetal tryptophan concentrations in IUGR (Lin et al, 2012) and suggested this might be because of impaired amino acid transport through the placenta (Avagliano et al, 2012). Although the previous proposition correlates with our data describing lower total tryptophan levels in SGA piglets, we cannot rule out that this latter finding is owing to a lower feed intake in these piglets (Devillers et al, 2007).…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, the AA transporter systems L and ASCT2 in the placenta of women with preeclampsia and intrauterine growth restriction (IUGR) are quite different from normal [22], suggesting that AAs may play an important role in the disease mechanism. Lower fetal concentrations of most AAs are observed in the umbilical cord and muscle of IUGR fetuses, compared with normal birth weight fetuses [12,23,24], demonstrating the impaired transport of AAs from the maternal to the fetal circulation in IUGR pregnancies. In our study, we first discovered that most of the AAs decreased in the CHD group, and strong associations were detected between AAs and CHD.…”
Section: Discussionmentioning
confidence: 99%